2016
DOI: 10.21521/mw.5606
|View full text |Cite
|
Sign up to set email alerts
|

Selected molecular and physiological aspects of mammalian ovarian granulosa cells in primary culture

Abstract: SummaryThe ovary is a complex endocrine gland that is responsible for sex steroid production in mammals. The basic functional unit of the ovary is the follicle, which contains the oocyte (OC), and surrounding cells, including granulosa cells (GCs) and theca cells, which support OC development. The process of formation and development of a follicle is known as folliculogenesis, during which the proliferation and differentiation of the GCs are required for proper formation of the follicle. In this review article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 43 publications
0
13
0
3
Order By: Relevance
“…Gonadotropin hormones, secreted from the pituitary, such as follicle stimulating hormone (FSH) and luteinizing hormone (LH) interact with receptors localized in the granulosa cells surrounding the oocyte, and thecal cells [19]. Research by Erickson et al showed that the growth of primary follicles is controlled mainly by local growth factors and proceeds independently of the level of hormones secreted from the pituitary gland [20].…”
Section: Physiological Basis Of Folliculogenesis In Mammalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gonadotropin hormones, secreted from the pituitary, such as follicle stimulating hormone (FSH) and luteinizing hormone (LH) interact with receptors localized in the granulosa cells surrounding the oocyte, and thecal cells [19]. Research by Erickson et al showed that the growth of primary follicles is controlled mainly by local growth factors and proceeds independently of the level of hormones secreted from the pituitary gland [20].…”
Section: Physiological Basis Of Folliculogenesis In Mammalsmentioning
confidence: 99%
“…The control of granulosa cell function by the oocyte takes place on the basis of feedback between both cell types. The gamete-somatic cell relation affects both the development of oocyte and ovarian follicles [19], [32].…”
Section: Factors Influencing Follicular Steroidogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside GCs are theca cells, ovarian surface epithelial (OSE) cells, and oocytes. Together, the Graafian follicle will form to protect the oocyte (folliculogenesis) and germ cells also mature into an egg (oogenesis) [2,3]. Granulosa cells have small cell-secreted vesicles called exosomes which are essential in mediating communication between cells, and they share this role with gap junctions [4].…”
Section: Introductionmentioning
confidence: 99%
“…Развитие фолликулов стимулирует рост стромально-сосудистого компонента органа. Она, в свою очередь, выполняя опорную и трофическую функцию, обеспечивает дифференциацию и сохранение пула половых клеток [5,17]. Развитие мозгового вещества также направлено на выполнение трофической функции.…”
unclassified